Do extra-pulmonary triggers or autonomic neural activity affect rhythm control by anti-arrhythmic drugs in patients with post-ablation atrial fibrillation recurrence? - Park, Hanjin; Yu, Hee Tae; Kim, Daehoon; Park, Je-Wook; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Hwang, Chun; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2024)
Background The role of anti-arrhythmic drugs (AADs) in recurrent atrial fibrillation (AF) after catheter ablation (CA) is not fully understood. The aim of this study was to explore the effects of AADs in patients who recurred after AFCA depending on extra-pulmonary vein triggers (ExPVTs) and post-ablation heart rate variability (HRV) parameters. Methods We analyzed 2,036 patients who underwent de-novo AFCA and 486 patients with post-AFCA recurrence who underwent rhythm control with AADs. We investigated the effects of ExPVTs and 3rd month HRV parameters on the post-AFCA recurrence and subsequent AAD responsiveness. Results A total of 486 out of 2,036 patients developed clinical recurrence of AF and subsequently underwent rhythm control with AADs. 486 out of 310 patients (63.8%) remained free of second recurrence at 1-year. Post-AFCA recurrence was significantly higher in patients with ExPVT [Log-rank p < 0.001, HR 1.45 (1.16–1.83), p = 0.001] or higher 3rd month root mean square of the differences between successive RR intervals (rMSSD) [Log-rank p < 0.001, HR 1.36 (1.11–1.65), p = 0.003] than their counterparts. Patients with ExPVTs during the de-novo procedure had significantly higher 3rd month rMSSD (15.0 [11.0–23.0] vs. 17.0 [11.0–28.0], p = 0.022). Patients with high 3rd month rMSSD had higher rate of ExPVTs during the repeat procedure (n = 160, 41.0% vs. 22.2%, p = 0.019). Among patients with recurrent AF after AFCA, post-AAD recurrence did not differ depending on the presence of ExPVT [Log-rank p = 0.455, HR 1.12 (0.78–1.69), p = 0.436] or 3rd month rMSSD [Log-rank p = 0.457, HR 1.16 (0.87–1.55), p = 0.300]. Post-AAD recurrence did not differ between class IC and III AADs (p for interaction = 0.311). Conclusions ExPVT and post-procedural high rMSSD are independent risk factors for post-AFCA recurrence but not for AAD response in patients with recurrent AF. AADs may suppress ExPVTs and modulate cardiac autonomic activity after post-AFCA recurrence.